The executive's book of quotations - Vitullo-Martin, Julia 1946-; Moskin, J. Robert (Oxford University Press, 1994)
This is a book of a wide variety of business-related quotations. Organized by subject and cross-indexed by authors/sources of quotes, the quotes are drawn from all periods - from Adam Smith to Michael Milken. There is a good mix of serious issues and the humorous side of business life.